Manajemen keuangan pendidikan berbasis digital: Sebuah kajian pustaka - Widodo, Trisno; Muhammad, Ilham; Darmayanti, Rani; Nursaid, Nursaid; Amany, Diella Aprilani Luthfia (Indonesian Journal of Educational Management and Leadership, 2023)
This research is motivated by the importance of Digital-based educational financial management. This study aims to analyze the concept of digital-based financial management. The method used in this research is descriptive qualitative. The purpose of this research is to analyze the concept of digital-based education financial management. This research is library research. Researchers collect data from various references such as books, journals, articles, and others. Researchers use data sources. The primary data source is in the form of books on digital-based education financial management. In addition, researchers use secondary data such as journals and scientific articles published in national and international journals. Collecting data with reading and note technique. Data analysis, researchers used Miles and Huberman's interactive analysis techniques, namely: (1) data reduction in the form of summarizing data and selecting data that is relevant to the topic of discussion; (2) data presentation in the form of presenting reduced data; and (3) drawing conclusions. The results of this study include 1) education financial management, 2) principles of digital-based education financial management, 3) implementation of digital-based education financial management. Overall, this research results in a better understanding of education finance management, the principles of digital-based education finance management, and their implementation.